2019
DOI: 10.1158/1055-9965.epi-18-0733
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Intestinal Metaplasia: A Cohort Study

Abstract: Background: We examined the association between body mass index (BMI) and development of endoscopic intestinal metaplasia.Methods: This retrospective cohort study included 142,832 Korean adults free of endoscopic intestinal metaplasia and atrophic gastritis who underwent upper endoscopy at baseline and subsequent visits and were followed for up to 5 years. A parametric proportional hazards model was used to estimate the adjusted HR with 95% confidence interval (CI) for incident intestinal metaplasia.Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…A recent large Korean study reported that obesity was independently associated with an increased incidence of GIM. 21 In our study, the univariate analysis did show an association between increasing BMI and a diagnosis of GIM. However, after adjusting for multiple variables, this association was no longer observed, and a negative association was observed for the obese (as defined by either the WHO classification and by quintiles).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…A recent large Korean study reported that obesity was independently associated with an increased incidence of GIM. 21 In our study, the univariate analysis did show an association between increasing BMI and a diagnosis of GIM. However, after adjusting for multiple variables, this association was no longer observed, and a negative association was observed for the obese (as defined by either the WHO classification and by quintiles).…”
Section: Discussionsupporting
confidence: 48%
“…17 However, understanding the association of PPI use with the development of GIM is complex, as histological examination is required and other multiple risk factors are associated with the diagnosis of GIM, such as H. pylori infection, increasing age, cigarette smoking, autoimmune gastropathy, alcohol consumption, bile reflux, a diet low in fruits and vegetables, obesity, high body mass index (BMI) and high salt intake. 2,[18][19][20][21] Hence, to clarify further the association between PPI use and the development of GIM, we conducted a retrospective endoscopic pathology-based study to assess whether PPI use is associated with the diagnosis of GIM while controlling for quantitative PPI use, H. pylori infection and multiple other risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that has been extensively examined in several observational studies is obesity, although results are mostly inconclusive [21][22]. Recently, a large cohort analysis by Kim et al [24] showed that obesity was associated with a higher incidence of AG and IM, with risk increasing as BMI category increased. In addition, the Korean study demonstrated that the positive association between BMI and IM was more evident in individuals younger than 40 years old, suggesting that accumulative exposure to other environmental factors may play a role in the prevalence of gastric cancer and its precancerous lesions with more advancing age.…”
Section: Premalignant Conditions and Gastric Cancermentioning
confidence: 99%
“…Gastric cancer was defined as gastric adenocarcinoma or signet ring cell carcinoma. Atrophic gastritis was defined as mucosal thinning with pale and shiny surface and visible submucosal vessels and intestinal metaplasia was defined as nodular elevated whitish plaques in the antrum or corpus [27,28]. H. pylori infection status was evaluated histologically only when indicated such as in the case of peptic ulcer disease, at the discretion of the endoscopist based on Korean guidelines [29].…”
Section: Data Collectionmentioning
confidence: 99%